Structural and Crystallographic Evolution of Nano-POFA using XRD-Based Crystallite Analysis - Masriah, Imas; Lestari, Devi; Sani, Sulwiyatul Kamariyah; Pangestika, Inten; Miswanda, Dikki (PUI BiGME Universitas Jambi, 2026)
Palm oil fuel ash (POFA) is one of the main by-products of the palm oil industry, predominantly composed of silica (SiO2) and various other metal oxides. Nano-POFA (P1) was synthesized using a top-down approach via high-energy ball milling process at a rotational speed of 1300 rpm for 1 hour using 4 mm-diameter milling balls. The X-ray diffraction patterns revealed that the dominant crystalline phases were Quartz (SiO2) and Mullite (Al6Si2O13), accompanied by minor phases such as Cristobalite (SiO2), Hematit (Fe2O3), Calcite (CaCO3), CaO, and Al2O3. The XRD analysis results of samples P0 (without ball milling) and P1 (1 hour of ball milling) revealed a significant decrease in peak intensity and peak broadening after 1 hour of the milling process. This phenomenon indicates partial amorphization and crystal fragmentation. The average crystallite size decreased from 92.14 nm in sample P0 to 47.52 nm in sample P1. These results indicate that the high-energy ball milling process induces lattice distortion, structural disorder, and amorphization within the Si-O framework of the POFA. The Williamson-Hall analysis indicated an increase in microstrain from ԑ=3.38 x 10-3 to ԑ=1.227 x 10-2. The structural transformations increase surface defect density and reactivity, signifying nano-POFA’s potential as material heterogenous catalyst for related chemical processes